The "How To" of Fiscal Sustainability : A Technical Manual For Using The Fiscal Sustainability Tool - Bandiera, Luca (The World Bank, 2007)
Fiscal sustainability analysis (FSA) is an important component of macroeconomic analysis for many developing countries. To further enhance understanding of fiscal policy and the constraints faced by policymakers, the authors develop a toolkit for FSA in middle-income countries which builds on previous work in this area and on new developments in dealing with uncertainty. The FSA toolkit includes an Excel-based FSA tool and a technical manual accompanying it. The FSA tool is standardized and simple, but at the same time flexible enough to allow for user-defined country-specifics. This manual provides step-by-step technical instructions for running the FSA tool and includes mathematical appendices and a glossary